2010
DOI: 10.1016/j.msea.2009.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of austenite retained in bainitic steels

Abstract: Steels with a microstructure consisting of a mixture of bainitic ferrite and carbon-enriched retained austenite are of interest in a variety of commercial applications because they have been shown to exhibit good combinations of strength, toughness and ductility. However, their use at temperatures moderately above ambient requires a knowledge of the thermal stability of the austenite. The changes that occur during the tempering of a mixture of bainitic ferrite, carbon-enriched retained austenite and martensite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 23 publications
6
105
0
1
Order By: Relevance
“…2(e) showed that the amount of carbides increased, ascribed to decomposition of retained austenite by a diffusion mechanism accompanying more precipitation of carbides. [24][25][26] or precipitation of carbides from austenite, which reduced austenite stability, resulting in transformation from austenite to martensite during cooling process, 19,27) thus the volume fraction and carbon concentrate of retained austenite drastically decreased to minimum as presented in Fig. 3.…”
Section: Precipitation and Dissolving Of Carbides And Variation Of Aumentioning
confidence: 99%
“…2(e) showed that the amount of carbides increased, ascribed to decomposition of retained austenite by a diffusion mechanism accompanying more precipitation of carbides. [24][25][26] or precipitation of carbides from austenite, which reduced austenite stability, resulting in transformation from austenite to martensite during cooling process, 19,27) thus the volume fraction and carbon concentrate of retained austenite drastically decreased to minimum as presented in Fig. 3.…”
Section: Precipitation and Dissolving Of Carbides And Variation Of Aumentioning
confidence: 99%
“…The resulting depletion of carbon in the retained austenite has been shown to lead to the formation of more ferrite, both during isothermal holding and during subsequent cooling. [20,21] It is expected that the high nickel content of Alloy 2 will prevent this transformation and allow the alloy to avoid carbide precipitation during thermal exposure.…”
Section: B Alloymentioning
confidence: 99%
“…Rapid decomposition of austenite into carbides and ferrite has been observed in nanocrystalline steels upon heating. [20,21] The resulting loss of austenite compromises both the strength and toughness of the steel and hence it is unsuitable for service at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: tanqibingmatin@126.com high strength-toughness drilling tool steel was systematic researched. Which was on the basis of study on the effects of rare earth elements in this kind of drilling tool steel sub-structure [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%